Health shocks and risk aversion - Simon Decker; Hendrik Schmitz (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2015)
Risk preferences are typically assumed to be constant for an individual across the life cycle. In this paper we empirically assess if they are time varying. Specifically, we analyse whether health shocks influence individual risk aversion. We follow an innovative approach and use grip strength data to obtain an objective health shock indicator. In order to account for the non-random nature of our data we employ regression-adjusted matching. Health shocks are found to increase individual risk aversion. The finding is robust to a series of sensitivity analyses. – – Risikopräferenzen werden typischerweise als konstant über den Lebenszyklus eines Individuums angenommen. In dieser Arbeit untersuchen wir diese Annahme empirisch. Konkret analysieren wir, ob Gesundheitsschocks den Grad individueller Risikoaversion beeinflussen. Hierbei verwenden wir die Greifkraft zur objektiven Messung von Gesundheitsschocks und regression adjusted matching. Im Ergebnis zeigt sich, dass Gesundheitsschocks den Grad individueller Risikoaversion erhöhen. Dieser Befund ist robust über eine Vielzahl von Sensitivitätsanalysen.
Keywords: C81; D01; D81; I10; I12; 330; risk preferences; health shocks; hand grip strength; regression-adjusted matching